Horizontal stress Field evolution from Eocene to present in Neuquen Basin - Guzmán, C.G. (2011)
Continuity and evolution in time of the horizontal stress direction in the Neuquen Basin area, derived from the analysis of recent borehole data and orientation of volcanic dykes measured in outcrop in the Cara Cura and Reyes Ranges is presented. The bitumen dykes along the Neuquén Basin were formed during Paleocene - Eocene in a context where the maximum stress was horizontal and had a NE. Within the analyzed volcanic dykes two major groups have been recognized, group i (NE orientation) and group ii (NNE orientation) and a secondary group iii (NW orientation). The age of these dykes is still not well established, but they were related to a Late Oligocene - Miocene magmatic event. Both for the volcanic and bitumen dykes a type i group (ENE-NE orientation) has been recognized, evidencing the maximum stress direction at the time they were formed. Beyond the uncertainties in the volcanic and bitumen dykes age, it is interpreted that during great part of Tertiary, the orientation of the horizontal maximum stress was NE. However, the breakout data shows that the actual horizontal maximum stress is a little different with a ENE mean direction. This change in the direction of stress is consistent with the change in the subduction vector produced between the Eocene and today.